Homeland. The complete seventh season [videorecording (DVD)] - Glatter, Lesli Linka; Klick, Michael; Danes, Claire, 1979-; Patinkin, Mandy; Patinkin, Mandy; Marvel, Elizabeth (Twentieth Century Fox Home Entertainment, 2019)
When a rescued POW returns home after eight years, a CIA agent begins to believe that the war hero may be a danger to America.